PEER FEEDBACK AS A STRATEGY FOR IMPROVING STUDENT’S TRANSLATION SKILL - Nunuk Tri Hapsari; Nugraha Krisdiyanta; Ismiati (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2022)
One of the processes that should be taken in the process of translation is reviewing the translation. This step must be taken before a translation product becomes the final text of the translation. In that process, peer feedback is needed. This article is research about the use of peer feedback in the process of reviewing student translations. The research was qualitative research. It was conducted based on the activities of a translation class in STBA LIA Yogyakarta. The research aims to see whether there is an improvement in the final results of student translations on their translation products based on their peer feedback. In this research, students are asked to translate some Indonesian texts into English. The translation then was given some comments and suggestions by their peers before they revised the translation to be the final product. The data were taken based on the students’ translation products. The peer feedback and Componential analysis theory are used as the basis of analysis in this research data analysis. The results showed that peer feedback could not be used as a basis for improving translation results due to the same difficulties among peers themselves over problems in the process of selecting and restructuring translating text from Indonesian as a source language to English as a target language. The role of the lecturer in this matter is still needed in Translation Class at STBA LIA Yogyakarta.